Antisense oligonucleotide targeting of thrombopoietin represents a novel platelet depletion method to assess the immunomodulatory role of platelets. (6th May 2020) - Barrett, Tessa J.; Wu, Benjamin G.; Revenko, Alexey S.; MacLeod, A. Robert; Segal, Leopoldo N.; Berger, Jeffrey S.
Abstract: Background: Platelets are effector cells of the innate and adaptive immune system; however, understanding their role during inflammation‐driven pathologies can be challenging due to several drawbacks associated with current platelet depletion methods. The generation of antisense oligonucleotides (ASOs) directed to thrombopoietin ( Tpo ) mRNA represents a novel method to reduce circulating platelet count. Objective: To understand if Tpo ‐targeted ASO treatment represents a viable strategy to specifically reduce platelet count in mice. Methods: Female and male mice were treated with TPO‐targeted ASOs and platelet count and function was assessed, in addition to circulating blood cell counts and hematopoietic stem and progenitor cells. The utility of the platelet‐depletion strategy was assessed in a murine model of lower airway dysbiosis. Results and Conclusions: Herein, we describe how in mice, ASO‐mediated silencing of hepatic TPO expression reduces platelet, megakaryocyte, and megakaryocyte progenitor count, without altering platelet activity. TPO ASO‐mediated platelet depletion can be achieved acutely and sustained chronically in the absence of adverse bleeding. TPO ASO‐mediated platelet depletion allows for the reintroduction of new platelets, an advantage over commonly used antibody‐mediated depletion strategies. Using a murine model of lung inflammation, we demonstrate that platelet depletion, induced by either TPO ASO or anti‐CD42b treatment, reduces the accumulation of inflammatory immune cells, including monocytes and macrophages, in the lung. Altogether, we characterize a new platelet depletion method that can be sustained chronically and allows for the reintroduction of new platelets highlighting the utility of the TPO ASO method to understand the role of platelets during chronic immune‐driven pathologies.